Courting Greta [large type] - Hootman, Ramsey (Thorndike Press large print core series., 2014)
The relationship between former computer programmer Samuel Cooke and tough-as-nails gym coach Greta Cassamajor has a chance of succeeding, but only if the two of them can stop keeping the past secret and finally be honest with each other.